2005
DOI: 10.1179/174328905x64731
|View full text |Cite
|
Sign up to set email alerts
|

Flow visualisation of water assisted injection moulding process

Abstract: This report investigates the filling phenomena of the water assisted injection moulding process by using a flow visualisation technique. Experiments were carried out on an 80-tonne injectionmoulding machine equipped with a laboratory-developed water injection unit. The material used was semi-crystalline polypropylene. A flow visualisation mould was specially designed and made for this study. A high-speed video camera was used to record the mould filling phenomena of rectangular cavities with three-channel geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In this work, the proportion of residual wall thickness was used to reflect the water penetration behavior, the proportion of residual wall thickness refers to the ratio of residual wall thickness at the selected position to the radius of mold cavity. As shown in Figure 7, the proportion of residual wall thickness varied greatly within the range of 40 mm from the water inlet, indicating that a very unstable penetration behavior occurred in this region, which is consistent with the previous investigations 12,13,48,49 . Besides, the melt would be quickly solidified once it touched water, and thus the fiber orientation can be preserved 33 .…”
Section: Resultssupporting
confidence: 87%
“…In this work, the proportion of residual wall thickness was used to reflect the water penetration behavior, the proportion of residual wall thickness refers to the ratio of residual wall thickness at the selected position to the radius of mold cavity. As shown in Figure 7, the proportion of residual wall thickness varied greatly within the range of 40 mm from the water inlet, indicating that a very unstable penetration behavior occurred in this region, which is consistent with the previous investigations 12,13,48,49 . Besides, the melt would be quickly solidified once it touched water, and thus the fiber orientation can be preserved 33 .…”
Section: Resultssupporting
confidence: 87%
“…However, as the melt was injected into the cavity, it quickly solidified once it touched the water inlet and tightly wrapped the water inlet, which caused the penetration behavior of water at position S1 to become unstable. With the decrease of melt temperature, the solidified layer of melt surrounding the water inlet became thicker, aggravating the unstable penetration behavior of high‐pressure water at this location, 55,56 which in turn induced the random alignment of more fibers. Thus, decreasing the melt temperature from 230 to 210°С led to a slight increase in the relative thickness of the ordered region at position S1.…”
Section: Resultsmentioning
confidence: 99%
“…Water penetration remains stable, and the residual wall thickness is uniform. Wu and Liu12,13 investigated the flow visualization of cavity‐filling process in WAIM by experiments, which showed that the penetration of water was quite steady and uniform during the whole filling process, and the water bubble kept almost the same diameter. The water penetration behaviors of simulations are in accord with experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…To make a comparison of the water penetration behavior and residual wall thickness of simulations and literatures,12–17 polypropylene (PP) is taken as a study resin in this article. Cross‐WLF viscosity model parameters of PP are shown in Table I, which are obtained form MOLDFLOW material library.…”
Section: Model and Methodsmentioning
confidence: 99%